The ECB and the interbank market - Domenico Giannone; Michele Lenza; Lucrezia Reichlin (European Central Bank (ECB), 2012)
We analyse the impact on the euro area economy of the ECB's non-standard monetary policy measures by studying the effect of the expansion of intermediation of interbank transactions across the central bank balance sheet. We exploit data drawn from the aggregated Monetary and Financial Institutions (MFI) balance sheet, which allows us to construct a measure of the `policy shock' represented by the ECB's increasing role as a financial intermediary. We find small but significant effects both on loans and real economic activity.
Keywords: E5; E58; 330; Interbank Market; Non-standard monetary policy measures